Review of investigations on fleas (Siphonap-tera) of mammals and birds in Ciscaucasia - Lyudmila Aleksandrovna Kot; Boris Konstantinovich Kotti (Наука. Инновации. Технологии)
The species history of diversity, distribution, parasite-host relations, sea-sonal rhythms of mammals’ and birds fleas investigations in Ciscaucasia is discussed. These items are known most for the rodents and insectivorous fleas, less - for fleas of other of mammals orders and parasites of birds